Incorporating Social Values Toward Islamic Education in Multicultural Society - Rohmat Mulyana (UIN Sunan Gunung Djati, 2023)
Enhancing students' understanding of social values in a multicultural society is crucial within Islamic education. This research employs a mixed-method approach, combining qualitative and quantitative analyses, to explore factors supporting incorporating social values into curriculums and teaching strategies. Lessons in Islamic studies and social studies are delivered experientially and contextually, influencing students' social attitudes toward diversity, including tolerance, patriotism, respect, and sympathy. The findings highlight the comprehensive impact of this integrated approach on shaping students' perspectives.